Analisis Efektivitas Kemitraan Ekonomi Komprehensif Regional (RCEP) terhadap Perekonomian ASEAN Pascapandemi: Indonesia - Ayuni, Nur Izzah (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2023)
The Regional Comprehensive Economic Partnership (RCEP) is a megaregional trade agreement consisting of 10 ASEAN countries and 5 non-ASEAN countries and was signed on November 20, 2020. The purpose of the RCEP agreement is to become a modern, comprehensive, high-quality economic agreement, forming a larger FTA. and progress beyond the ASEAN+1 FTA, and can be mutually beneficial for ASEAN and East Asian countries. Through the RCEP agreement, it is hoped that it can be a gradual driving force to overcome the economy of ASEAN countries in the post-pandemic period through rules or regulations that have been set together. This paper will discuss the effectiveness of RCEP in the post-pandemic ASEAN economy. The method used in this paper is derived from a literature study. The data obtained will then be linked to the theory of the effectiveness of the international regime. RCEP succeeded in becoming a set of official and binding rules and member countries in the agreement followed mutually agreed rules or regulations. The outcomes issued by RCEP did not all have a positive impact, but there were obstacles which later affected the impact and effectiveness of this agreement. There are several factors that influence the outcome of the agreement, one of them is the state of the domestic economy and the different industrial structure of each country which then each country has different advantages in each country Keywords: ASEAN, Effectiveness, Post-Pandemic, RCEP